Effect of orthokeratologic lenses of individual design on visual functions in premature babies with myopia in school age - Serdiuk , V.M.; Ustymenko , S.B.; Klopotska , N.G.; Tikhomirova , V.V. (Medicni Perspektivi, 2022)
The study included 62 children aged 6 to 14 years with mild to moderate myopia, born at 28-34 weeks of gestation with a birth weight of 970 to 2200 g. Selection criteria: corneal refractive power >46.00 D, no keratoconus or macular degeneration. The main group – 32 children (64 eyes), who were assigned orthokeratologic lenses, the control group – 30 children (60 eyes) – glasses users. Differences between the groups were not significant. Observation period was 3 years. There were no complications. Corrected visual acuity in the main group increased from 0.63±0.08 to 0.98±0.06, in the control – from 0.61±0.05 to 0.73±0.05; p<0.005. Stable restoration of binocular vision was observed in all children of the study group and 83% of children in the control one. Reserves of absolute accommodation in the main group during the observation period increased by 6.7±0.38 D, and in the control group – by 2.3±0.42 D (p<0.001), which is explained by the active use of accommodation by children of the main group. After 3 years of observation in the main group, the anteroposterior size of the eyeball, according to echobiometry data, almost did not change (from 22.32±0.9 to 24.02±1.1 mm, p>0.2), and in the control group, the eye elongation was more pronounced: from 22.45±0.8 to 25.94±0.9 mm (p<0.01). Complete stabilization of myopia was observed in 30 children (93.75%) of the study group. Orthokeratological lenses MoonLens can be used in patients with high corneal curvature; their use in prematurely babies with a high refractive power of the cornea (>46.0 D) allowed to obtain better results of the treatment.